A randomized comparison of oral chloramphenicol versus ofloxacin in the treatment of uncomplicated typhoid fever in Laos. - Phongmany, S; Phetsouvanh, R; Sisouphone, S; Darasavath, C; Vongphachane, P; Rattanavong, O; Mayxay, M; Ramsay, A; Blacksell, S; Thammavong, C; Syhavong, B; White, N; et al. (2005)
We conducted a randomized open trial of oral chloramphenicol (50mg/kg/day in four divided doses for 14 days) versus ofloxacin (15 mg/kg/day in two divided doses for 3 days) in 50 adults with culture-confirmed uncomplicated typhoid fever in Vientiane, Laos. Patients had been ill for a median (range) of 8 (2-30) days. All Salmonella enterica serotype typhi isolates were nalidixic acid-sensitive, four (8%) were chloramphenicol-resistant and three (6%) were multidrug-resistant. Median (range) fever clearance times were 90 (24-224) hours in the chloramphenicol group and 54 (6-93) hours in the ofloxacin group (P<0.001). One patient in the chloramphenicol group developed an ileal perforation. Three days ofloxacin was more effective than 14 days chloramphenicol for the in-patient treatment of typhoid fever, irrespective of antibiotic susceptibility, and was of similar cost.